High-frequency current welding using suprachoroidal approach to treat retinal tears: study of safety and efficacy. - Уманець, Микола Миколайович (My University, 2023)
PURPOSE. Chorioretinal adhesions (CRA) are essential in retinal detachment surgery. To evaluate the morphological changes (MC) and CRA strength (CRAS), a high-frequency electric current welding (HFECW) was applied with suprachoroidal approach on experimental animal model to cause CRA. METHODS. For HFECW, a modified generator EK-300M1 (E.O. Paton Electric Welding Institute, Kyiv, Ukraine) with pre-settings (66 kHz, three groups: 10-12 Volts (V), 12-14 V and 14-16 V) was used. Treated eyes were enucleated in 1 hour (h), 3, 7, 14 and 30 days after treatment A study of the MC of the CRA was performed on 54 (108 eyes) adult chinchilla rabbits (32 eyes per group, 12 control eyes); the retina was treated 7-10 mm posterior to the limbus through a U-shaped scleral incision with suprachoroidal approach using 25-gauge tip (treated area diameter/size 0.260 mm/0.053 mm2). The eyes were analyzed using H&E staining and light microscopy. Study of CRAS was performed on 52 (104 eyes) rabbits: (32 eyes per group, 8 control eyes). CRAS was measured using a biomechanical force elongation tester. The reduction in weight at the time of CRA rupture was registered as a measure for adhesion strength. RESULTS. The study of CRAS showed that after application of 10-12 V at 1 h from treatment with HFECW a CRAS was 8.75% and 25.74% higher than that of 12-14 V and 14-16 V, respectively. and at 1 week from treatment was 10.18% and 9.54% higher than that of 12-14 V and 14-16 V, respectively. The MC showed an instant increase in the CRA in the area of HFECW application, which further strengthened with time. The retina responded by apparent destruction of rods, cones, loss of bipolar, amacrine, horizontal and ganglion cells, development of cysts and migration of RPEs, while the choroid showed damage and migration of melanocytes. By day 30, a ​​tissue reaction showed a partial cell regeneration and connective tissue degeneration. Adjacent retina remained intact. CONCLUSIONS. Application of HFECW with suprachoroidal approach can induce an instant CRA, which strengthens within first weeks from surgery. Application of lower electromotive force (10-12 V) showed a higher CRA strength. HFECW with suprachoroidal approach could be an alternative method to treat retinal tears, reducing the need for endotamponade and vitreoretinal surgery.